Maternal outcome in premature rupture of membrane - a study done in the tertiary Level specialized hospital in Bangladesh - Adhikary, Sanchita; Tanira, Shaorin; Sultana, Arifa; Wazed, Feroza; Chowdhury, Saleha Begum (Journal of Dhaka Medical College, 2013)
Context: Premature rupture of membrane is defined as spontaneous rupture of membrane before the initiation of labour, which is one of the most common complications of pregnancy having a major impact on maternal outcome. The aim of the present study is to find out the effect of premature rupture of membrane on maternal outcome. Methods: A cross-sectional study was done in the Department of Obstetrics and Gynaecology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from February to July of 2008, on 50 pregnant women with more than 28 weeks of pregnancy both primigravid and multigravid with rupture of membranes prior to labour. Women who were admitted with rupture of membranes with established labour, or having antepartum haemorrhage, pre-eclampsia or eclampsia were excluded from the study. Out of 775, 95 patients were admitted with history of premature rupture of membrane (PROM). Among those patients, 50 cases were included in this study as per inclusion and exclusion criteria. Results: In this study, onset of labour was spontaneous in 30 cases (60%), 35 cases (70%) developed labour within 24 hours of rupture of membranes and 2 patients (4%) had latent period exceeding 7 days. Among those 50 patients, 24 i.e. 48% (primigravida 12 and multigravida 12) had normal vaginal delivery and 26 i.e. 52% (primigravida 16 and multigravida 10) underwent Caesarean section. 5 patients (10%) developed puerperal sepsis (primigravida 1 and multigravida 4). DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15600 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 26-29